Evaluating Osteogenic Differentiation of Osteoblastic Precursors Upon Intermittent Administration of PTH/IGFBP7 - Xia, Han; Tian, Yueyang; Lin, Yile; Huang, Qia; Xue, Yuan (Frontiers in Pharmacology, 2022)
Parathyroid hormone (PTH) 1-34 is the first anabolic agent approved for the treatment of osteoporosis. Preclinical evidence shows a potential association between PTH and osteosarcoma. The mechanisms mediating the bone- and neoplasm-forming effects of PTH remain incompleted understood. Insulin-like growth factor-binding protein 7 (IGFBP7) is implicated as a tumor suppressor and may promote osteogenic differentiation of stem cells and fibroblasts. Few studies on the role of IGFBP7 in mediating the anabolic effects of PTH has been reported. Intermittent PTH administration was found to increase the expression of IGFBP7 in mesenchymal stem cells (MSCs) and pre-osteoblasts. Our results indicated that the anabolic effects of PTH were interrupted when knockdown of IGFBP7, while supplementation with IGFBP7 protein could enhance the bone-forming efficacy of PTH and regulate the signaling pathways. Moreover, bone healing was accelerated by the administration of IGFBP7 along with PTH in a mouse model of fracture. These findings revealed that IGFBP7 was necessary for the anabolic effects of PTH, and combined administration of PTH and IGFBP7 showed stronger bone-forming effects relative to administration of PTH alone.